Roles for osteocalcin in proliferation and differentiation of spermatogonial cells cocultured with somatic cells. Issue 4 (9th October 2018) - Solhjoo, Somayeh; Akbari, Mohammad; Toolee, Heidar; Mortezaee, Keywan; Mohammadipour, Mahshid; Nematollahi‐Mahani, Seyed Noureddin; Shahrokhi, Amene; Sayadi, Mahtab; Rastegar, Tayebeh
Abstract: Spermatogonial cells (SCs) are key cells for spermatogenesis. These cells are affected by paracrine signals originated from nearby somatic cells, among them Leydig cells have receptors for osteocalcin, a hormone known for exerting positive roles in the promotion of spermatogenesis. The aim of this study was to evaluate roles for osteocalcin on SCs proliferative and differentiation features after coculture with Leydig cells. SCs and Leydig cells were isolated from neonate NMRI offspring mice and adult NMRI mice, respectively. SCs population were then enriched in a differential attachment technique and assessed for morphological features and identity. Then, SCs were cocultured with Leydig cells and incubated with osteocalcin for 4 weeks. Evaluation of proliferation and differentiation‐related factors were surveyed using immunocytochemistry (ICC), Western blot, and quantitative real‐time polymerase chain reaction (PCR). Finally, the rate of testosterone release to the culture media was measured at the end of 4th week. Morphological and flow cytometry results showed that the SCs were the population of cells able to form colonies and to express ID4, α6‐, and β1‐integrin markers, respectively. Leydig cells were also able to express Gprc6α as a specific marker for the cells. Incubation of SCs/Leydig coculture with osteocalcin has resulted in an increase in the rate of expressions for differentiation‐related markers. Levels of testosterone in the culture media of SCs/Leydig was positively influenced by osteocalcin. It could be concluded that osteocalcin acts as a positive inducer of SCs in coculture with Leydig cells probably through stimulation of testosterone release from Leydig cells and associated signaling. Abstract : Spermatogonial cells (SCs) affected by paracrine signals originated from nearby somatic cells. The aim of this study was to evaluate roles for osteocalcin on SCs proliferative and differentiation features after coculture with somatic cells. We concluded that osteocalcin acts as a positive inducer of SCs in coculture with Leydig cells probably through stimulation of testosterone release from Leydig cells and associated signaling.